Enfoque Analítico en la Clasificación de Vulnerabilidades CVE y la Identificación de Amenazas a través del Registro Malicioso en DNS. - Briones Ronquillo, Rubén Jacinto (2024)
The analytical focus on classifying CVE vulnerabilities and identifying threats through malicious DNS registration is essential to strengthen cybersecurity in network environments and communication protocols. This study focuses on the application of data analysis techniques to understand the nature and impact of known vulnerabilities, as well as to detect indicators of compromise through DNS traffic. By integrating information from the CVE database with DNS records, abnormal behavior patterns and correlations can be identified that help prevent and mitigate potential attacks. This analytical approach provides a holistic view of online threats, allowing cybersecurity professionals to make informed and proactive decisions to protect networks and communication systems.